Tracking sediment provenance and erosional evolution of the western Greater Caucasus. Issue 8 (8th April 2014) - Vezzoli, Giovanni; Garzanti, Eduardo; Vincent, Stephen J.; Andò, Sergio; Carter, Andrew; Resentini, Alberto
ABSTRACT This article investigates landscape characteristics and sediment composition in the western Greater Caucasus by using multiple methods at different timescales. Our ultimate goal is to compare short‐term versus long‐term trends in erosional processes and to reconstruct spatio‐temporal changes in sediment fluxes as controlled by partitioning of crustal shortening and rock uplift in the orogenic belt. Areas of active recent uplift are assessed by quantitative geomorphological techniques [digital elevation model (DEM) analysis of stream profiles and their deviation from equilibrium] and compared with regions of rapid exhumation over longer time intervals as previously determined by fission‐track and cosmogenic‐nuclide analyses. Complementary information from petrographic and heavy‐mineral analyses of modern sands and ancient sandstones is used to evaluate erosion integrated throughout the history of the orogen. River catchments displaying the highest relief, as shown by channel‐steepness indices, correspond with the areas of most rapid exhumation as outlined by thermochronological data. The region of high stream gradients is spatially associated with the highest topography around Mount Elbrus, where sedimentary cover strata have long been completely eroded and river sediments display the highest metamorphic indices and generally high heavy‐mineral concentrations. This study reinforces the suggestion that the bedrock–channel network can reveal much of the evolution of tectonically active landscapes, and implies that the controls on channel gradient ultimately dictate the topography and the relief along the Greater Caucasus. Our integrated datasets, obtained during a decade of continuing research, display a general agreement and regularity of erosion patterns through time, and consistently indicate westward decreasing rates of erosional unroofing from the central part of the range to the Black Sea. Copyright © 2014 John Wiley & Sons, Ltd.